Prophetic Supervision and the Strengthening of Quality Culture in Islamic Education: Evidence from MAN Kotawaringin Timur, Indonesia - Achmad Robita; Dakir Dakir (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyze how prophetic supervision contributes to the transformation and strengthening of quality culture in Islamic education at MAN Kotawaringin Timur. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using thematic analysis to identify key patterns of change in the institution’s quality practices. The findings reveal several core aspects of cultural transformation: the strengthening of a value-based quality culture; the growth of teachers’ moral and professional motivation; the emergence of transformative leadership through spiritually grounded supervision; increased teacher participation in professional development; and the institutionalization of continuous improvement supported by reflective religious practices. The study concludes that prophetic supervision effectively integrates technical guidance with moral-spiritual development, shaping a more ethical, collaborative, and improvement-oriented educational environment. Theoretically, this research contributes to the development of Islamic educational supervision by demonstrating how prophetic values can serve as a practical framework for enhancing quality culture. Practically, it offers a model for madrasah leaders to implement spiritually rooted supervision strategies that reinforce professionalism and institutional cohesion. The novelty of this study lies in its empirical demonstration of how prophetic supervision operates as a cultural transformation mechanism within Islamic educational institutions, an area that has received limited attention in previous research.